Hutchison's paediatrics - Goel, Krishna M.; Gupta, Devendra K. (Jaypee Brothers Medical Publishers, 2012)
Fully updated and extended new edition, presenting practical advice on diagnosis, investigation and treatment of childhood disorders. Covers broad spectrum of conditions in all parts of the body and includes four new chapters.